Open Government and (Linked) (Open) (Government) (Data) - Christian Philipp Geiger; Jörn von Lucke (JeDEM - eJournal of eDemocracy & Open Government, 2012)
This article explores the opening and the free usage of stored public sector data, supplied by state. In the age of Open Government and Open Data it’s not enough just to put data online. It should be rather weighed out whether, how and which supplied public sector data can be published. Open Data are defined as stored data which could be made accessible in a public interest without any restrictions for usage and distribution. These Open Data can possibly be statistics, geo data, maps, plans, environmental data and weather data in addition to materials of the parliaments, ministries and authorities. The preparation and the free access to existing data permit varied approaches to the reuse of data, discussed in the article. In addition, impulses can be given for Open Government – the opening of state and administration, to more transparency, participation and collaboration as well as to innovation and business development. The Open Data movement tries to get to the bottom of current publication processes in the public sector which could be formed even more friendly to citizens and enterprises.